DEVELOPMENT OF THE PENTAHELIX ECOSYSTEM AS A STRATEGY FOR OPTIMIZING LEADING MARINE COMMODITIES AND VILLAGE FISHERIES IN INDONESIA - Afdal, Muh. (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This paper discusses the Development of the Pentahelix Ecosystem as a Strategy in Optimizing the leading commodities of marine and village Fisheries in Indonesia. The potential of Indonesia's fisheries sector is the largest in the world, both capture fisheries and aquaculture so a strategy is needed to be able to optimize this potential. The Pentahelix model can be used as a strategy to encourage continuous collaboration in an effort to optimize the potential of marine and fisheries commodities in Indonesia. The problem examined in this study is how to develop a pentahelix collaboration model in encouraging the optimization of marine commodities and village fisheries in Indonesia. The method used is qualitative descriptive regarding model development analysis by referring to information obtained from various reliable sources referred to based on research objectives. Based on the data obtained, there are three problems in optimizing marine and fisheries commodities, namely limited market access and connection, limited technology and competence (HR) and lack of capital or funding. Based on these problems, it is urgent that the collaboration ecosystem model developed should be able to overcome these challenges.